A new pedal system measuring forces in three dimensions - Alexander, N.; Christian, J.; Jenny, H.; Augustin, H.; Schwameder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to analyse the accuracy of a new pedal system (CycPed) measuring forces in anterior-posterior, medio-lateral and vertical direction by using strain gauges. The forces measured with the pedal were compared in different dynamic situations with two different systems, SRM Powermeter and PowerForce. The CycPed data was converted in radial and tangential forces and pedal torque and power output were calculated. Pedal forces, torque and power output were in good agreement with the corresponding data gained from the SRM Powermeter and PowerForce. The pedal is light weight and data transmission could be implemented by using Bluetooth offering a good device for field measurements in cycling, which could be advantageous for athletes, coaches and scientist.